Integrated regional water management: the new direction in California - Macaulay, Steve, author; Borcalli, Francis, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Water resource planning is approached classically on a project-by-project basis, with an increasing trend towards multiple-benefit projects. Multiple-jurisdiction projects have been more the exception than the rule, largely due to a lack of shared interests, time lines, financing and other factors. Integrated regional water management (IRWM) is a recent phenomenon in California. This concept embodies the integration of a wide range of strategies, management tools and institutions to address water supply reliability, ecosystem enhancement, water quality and other natural resource issues. The IRWM focus is on addressing areas of common concern among a number of interests within a region, whether that region is defined by political, institutional or watershed boundaries. It has proven to be a successful strategy driven by development and population increases, a growing interest in protecting natural species habitat, and the need to diversify water supplies to strengthen water supply reliability for all uses. This paper describes the evolution of IRWM, from successful programs initiated at the local level to endorsement of the concept for statewide use in the 2005 California Water Plan Update. The paper addresses how the State of California is encouraging IRWM at both the policy and funding levels. We provide an overview of current IRWM planning and implementation throughout California. The Yolo County IRWM Plan is a case study of a successful collaborative effort to enhance water supply reliability — quantity and quality — for urban, agricultural, environmental, and recreational uses while addressing a range of issues related to ecosystem enhancement, flood risk management, and recreation.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.